WOMEN IN Y.B. MANGUNWIJAYA'S BURUNGBURUNG RANTAU: A CRITICAL DISCOURSE ANALYSIS - Tengsoe Tjahjono (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
According Kundera, a novel is not convention but is a writer's investigation of experience in the pitfalls of life. A novel can be used to discuss the issues of women and gender. One novel that explores the issue of women is Burung-burung Rantau by YB Mangunwijaya. There are three social processes in the formation of women's realities, namely: construction, deconstruction and reconstruction. Burungburung Rantau successfully portrays the practice of construction, deconstruction and reconstruction of the reality of women. Yuniati reflects the female construction of a mature woman, while Anggraini and Marineti undergo the process of deconstruction and reconstruction. Anggraini is hesitant in making decisions, while Marineti tends to be confident in her choices. The practice of construction, deconstruction and reconstruction of speech acts can be seen in the dialogues of the characters in the novel. They are also evident in the choice of words, figure of speech, and sentence structures used in the frame of discourse, power, inequality, and gender perspectives.